Eine Abbildung von Giuseppe (Joseph) Passalacqua, dem ersten Direktor des Ägyptischen Museums in Berlin - Moje, Jan (Zeitschrift für ägyptische Sprache und Altertumskunde, 2019)
Identification of the currently sole known image of Giuseppe (Joseph) Passalacqua, the first director of the Egyptian Museum in Berlin